Measuring health in inmates using a synthetic index: a study of a prison in central Italy - Altobelli, Emma; Galassi, Francesca; Proietti, Ilenia; Petrocelli, Reimondo; Marziliano, Ciro (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Global prison population has increased worldwide by approximately 24% since the 2000s. The objective of our study was to create a health status index for inmates at the L'Aquila prison and to describe their health profiles. Methods: The pathologies examined concerned: heart valves, arterial ischemia, cerebral vascular accidents, endocrine diseases, Type 2 diabetes, malignant and benign neoplasms. In addition, respiratory, kidney, urogenital, osteo-articular, gastrointestinal, neurological, anemia, otorhinolaryngology, ophthalmology, dermatological, dental, psychiatric disorders, and infectious diseases. A score was given to the therapies: 0-absence of therapy; 1-monotherapies; 2-polytherapies; 3-high-cost therapies. The health state was: good, fairly good, poor, compromised, severe, or loss of patient autonomy. The pathologies taken into consideration were introduced into the MCA model to highlight health profiles.Results: The synthetic health index showed the following health status: good (25 cases, 15.9%), fairly good (104, 66.2%), poor (25, 15.9%), compromised (2, 1.3%) and severe (1, 0.6%).The MCA identified three profiles. The first consisted of individuals aged ≥60, with the presence of arterial hypertension, respiratory diseases, cardiovascular diseases, endocrine diseases, neoplasms, and serious health status. The second, were inmates aged 50 to 59, with renal, gastrointestinal, neurological and infectious diseases, undergoing psychological treatment, with an average health status index. The third consisted of individuals under 50 with no underlying health conditions.Discussion: prevention must be a priority among young people in good health, to prevent their well-being from declining to a fair level, and above all, to prevent further deterioration into mediocre conditions.  In conclusion early intervention with preventive measures allows young prisoners to maintain optimal health, reducing the risk of developing chronic diseases or complications over time.